2012
DOI: 10.1177/0363546512447932
|View full text |Cite
|
Sign up to set email alerts
|

Greater Axial Trough Obliquity Increases the Risk of Graft Extrusion in Lateral Meniscus Allograft Transplantation

Abstract: The risk of graft extrusion increases as the axial plane trough angle increases. The angle can be reduced by ensuring that the bony trough starting point is not created in too lateral a position.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
100
4

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(108 citation statements)
references
References 22 publications
4
100
4
Order By: Relevance
“…Other studies showed that in the bone bridge technique, the risk of graft extrusion increases as the angle of the trough on the axial plane increases. 16 Jeon et al 17 suggested that the excision of a peripheral osteophyte larger than 2 mm in the proximal tibial plateau was associated with less MAT extrusion. Some surgeons fix the meniscus body to the tibial plateau in an attempt to control graft extrusion.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies showed that in the bone bridge technique, the risk of graft extrusion increases as the angle of the trough on the axial plane increases. 16 Jeon et al 17 suggested that the excision of a peripheral osteophyte larger than 2 mm in the proximal tibial plateau was associated with less MAT extrusion. Some surgeons fix the meniscus body to the tibial plateau in an attempt to control graft extrusion.…”
Section: Discussionmentioning
confidence: 99%
“…17 However, the 3 aforementioned studies overlooked the anatomic graft position on the sagittal plane. [15][16][17] To our knowledge, our study is the first to measure sagittal graft position after MRI obtained immediately after lateral MAT.…”
Section: Effect Of Sagittal Allograft Positionmentioning
confidence: 99%
“…17 However, the 3 aforementioned studies overlooked the anatomic graft position on the sagittal plane. [15][16][17] To our knowledge, our study is the first to measure sagittal graft position after MRI obtained immediately after lateral MAT. The results showed that the anterior horn position was more extruded from the anterior tibial articular margin and that the posterior horn position was more intruded from the posterior tibial articular margin in the lateral MAT group than in the control group, indicating that the position of the allograft was more anterior than the normal lateral meniscus.…”
Section: Effect Of Sagittal Allograft Positionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, during every surgical step of the meniscal allograft transplantation, our best efforts have to be focused on prevention of extrusion of the meniscal allograft. Recently published articles emphasized the importance of anatomical placement of the lateral meniscal allograft to decrease postoperative extrusion 56). Here, we present a patient who underwent a lateral meniscal transplantation using a wire that was formed to the contour of the allograft for correct graft placement.…”
mentioning
confidence: 99%